Does More Power for Shareholders Undermine Board Stewardship? - World Bank (World Bank, Washington, DC, 2012)
The level of shareholders' expertise and experience needs to be questioned as they wield greater clout and become more deeply involved in strategic issues that should be the board's purview. This misdirected involvement distracts shareholders from their principal and most important role: electing and overseeing boards. To play that role, shareholders must have the basic tools from soliciting proxies of holders of voting securities to having the ability to seek court relief for a company's oppressive conduct. One of the important principles of good governance is the empowerment of shareholders. Unless they are able and willing to hold boards to account, then there is little hope, short of tough and intrusive regulation, of ensuring that company management acts in anything other than their own narrow self-interest. But the question is: how far should shareholders go? Peter Dey's paper brings an important perspective of someone who is both committed to good governance and experienced as a corporate director. This report heralded a new era of increased attention to the responsibilities of Canadian boards as stewards of shareholder value. Internationally, the author has been associated with the International Corporate Governance Network (ICGN) for the last ten years and has been an active participant in the Global Corporate Governance Forum, serving as a chairman.